2001
DOI: 10.1073/pnas.261560998
|View full text |Cite
|
Sign up to set email alerts
|

Different responses of astrocytes and neurons to nitric oxide: The role of glycolytically generated ATP in astrocyte protection

Abstract: It was recently proposed that in Jurkat cells, after inhibition of respiration by NO, glycolytically generated ATP plays a critical role in preventing the collapse of mitochondrial membrane potential (⌬m) and thus apoptotic cell death. We have investigated this observation further in primary cultures of rat cortical neurons and astrocytes-cell types that differ greatly in their glycolytic capacity. Continuous and significant (Ϸ85%) inhibition of respiration by NO (1.4 M at 175 M O2) generated by [(z)-1-[2-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
312
2
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 377 publications
(347 citation statements)
references
References 28 publications
27
312
2
4
Order By: Relevance
“…Transient MHP is an early event preceding caspase activation, phosphatidylserine (PS) externalization, and disruption of Δψ m in Fas- [6] and H 2 O 2 -induced apoptosis of Jurkat human leukemia T cells and normal human peripheral blood lymphocytes (PBL) [8]. These observations were widely confirmed and extended to other apoptosis pathways [9,10,11,12,13,14]. Transient MHP is also triggered by activation of T cells by Con A [6] and CD3/CD28 costimulation [15] via ROI-and Ca 2+ -dependent production of NO [16].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Transient MHP is an early event preceding caspase activation, phosphatidylserine (PS) externalization, and disruption of Δψ m in Fas- [6] and H 2 O 2 -induced apoptosis of Jurkat human leukemia T cells and normal human peripheral blood lymphocytes (PBL) [8]. These observations were widely confirmed and extended to other apoptosis pathways [9,10,11,12,13,14]. Transient MHP is also triggered by activation of T cells by Con A [6] and CD3/CD28 costimulation [15] via ROI-and Ca 2+ -dependent production of NO [16].…”
Section: Introductionmentioning
confidence: 84%
“…Ibiza and colleagues recently showed that within minutes of binding to antigen, T cells produce NO via endothelial NO synthase (eNOS) [39]. NO promoted mitochondrial hyperpolarization, ATP depletion and relative resistance to apoptotic stimuli in astrocytes, lymphocytes and Jurkat cells [13,40]. Although pretreatment of normal T cells with NO resulted in elevation of mitochondrial and cytoplasmic Ca 2+ levels, Ca 2+ by itself was insufficient to induce NO synthesis or mitochondrial hyperpolarization in lymphocytes [16,39].…”
Section: Role Of Nitric Oxide In T Cell Activation Mitochondrial Biomentioning
confidence: 99%
“…NO promoted mitochondrial hyperpolarization, ATP depletion, and relative resistance to apoptotic stimuli in astrocytes, lymphocytes, and Jurkat cells [46,47]. Moreover, pretreatment of normal T cells with NO resulted in elevation of mitochondrial and cytoplasmic Ca 2+ level [43].…”
Section: Role Of Nitric Oxide In T Cell Activation Mitochondrial Biomentioning
confidence: 98%
“…Mitochondrial function is very sensitive to the presence of nitric oxide (Brown, 1995;Borutaite and Brown, 1996;Lizasoain et al, 1996;Giulivi, 1998;Brookes et al, 1999;Brown, 1999) and the mechanism by which NO induces apoptosis in several cell types appears to encompass changes in mitochondrial membrane potential (Dc m ) (Almeida et al, 2001;Bal-Price and Brown, 2000;Brorson et al, 1999;Solenski et al, 2003). To investigate the alteration of Dc m in PC-12 cells treated with DOPAC, SNAP or DOPAC plus SNAP, the fluorescent probe RH 123 was used as described in Section 2.…”
Section: Mitochondrial Membrane Potential and Atpmentioning
confidence: 99%